Respiratory Syncytial Virus in Hematopoietic Stem Cell Transplantation: Risk Stratification and Outcomes. (4th October 2017) - Abbas, Hashim; Rybicki, Lisa; Abounader, Donna; Mossad, Sherif; Majhail, Navneet; Cober, Eric
Abstract: Background: In hematopoietic stem cell transplant (HSCT) recipients, respiratory syncytial virus (RSV) can progress from upper respiratory tract infection (URTI) to lower respiratory tract infection (LRTI), causing substantial morbidity and mortality. At our center, we target treatment (aerosolized vs. oral ribavirin) to the "highest" risk patients based on a local treatment guideline. Subsequently, an immunodeficiency scoring index for respiratory syncytial virus (ISI-RSV), has been published. Our objective was to identify the risk factors for progression from URTI to LRTI and mortality, particularly ISI-RSV score and ribavirin treatment received. Methods: We reviewed forty adult HSCT recipients at the Cleveland clinic with RSV infection from January 2000 to December 2014, 28 presented with URTI and received oral ribavirin and 13 received inhaled ribavirin. Variables collected included those used to calculate ISI-RSV (in table), ribavirin treatment, and death, among others. The ISI- RSV score include: low-risk 0–2, intermediate risk 3–6, high-risk 7–12. Progression to LRTI was estimated with cumulative incidence and risk factors identified with Fine and Gray regression. Survival was estimated with Kaplan-Meier and prognostic factors identified with Cox proportional hazards analysis. Results are presented as hazard ratio (HR) and 95% confidence interval (CI). Results: Progression from URTI to LRTI occurred in 6 of 28 patients. Higher ISI-RSV score increased the risk of progression (HR 1.50, CI 1.02–2.18,  =  P = 0.037) but not death (HR 1.07, CI 0.86–1.34, P = 0.55). The use of oral ribavirin did not increase risk of progression (HR 1.06, CI 0.13–8.67, P = 0.96) or death. Conclusion: The ISI-RSV did predict progression from URTI to LRTI, but initial treatment with oral ribavirin instead of aerosolized did not. Limitations of this study include small sample size and low rate of the primary outcome, progression to LRTI. Future studies should focus on early identification and therapeutic interventions to prevent progression to LRTI. Disclosures: All authors: No reported disclosures.